2023
DOI: 10.1111/pin.13323
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma with aggressive fused follicular and solid growth pattern: A unique histological subtype with high‐grade malignancy?

Abstract: Papillary thyroid carcinoma (PTC) is usually indolent; however, some rare subtypes of PTCs, such as columnar cell and hobnail subtypes, carry poor prognosis as an intermediate malignancy between differentiated carcinoma and anaplastic carcinoma. We present the case of a 56‐year‐old Japanese woman having PTC with aggressive behavior showing characteristic histological features of a predominantly fused follicular and focally solid (FFS) pattern. The fused follicular pattern is cribriform‐like without intermingle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Another study from Thompson et al reported ki67 proliferation index values calculated for DHGTC ranging from 2.3 to 19.6%, with a median of 8.3% and an average of 9.4% in their study performed on 41 subjects [26]. In their case study of DHGTC, Murata et al reported a ki67 proliferation index value of 10%, higher than the aforementioned value [27].…”
Section: The Ki67 Proliferation Index In Relation To Genetic and Mole...mentioning
confidence: 88%
“…Another study from Thompson et al reported ki67 proliferation index values calculated for DHGTC ranging from 2.3 to 19.6%, with a median of 8.3% and an average of 9.4% in their study performed on 41 subjects [26]. In their case study of DHGTC, Murata et al reported a ki67 proliferation index value of 10%, higher than the aforementioned value [27].…”
Section: The Ki67 Proliferation Index In Relation To Genetic and Mole...mentioning
confidence: 88%